History of a failure and a refoundation?: Of the old to the new extreme right in Spain (1975-2012) - José Luis RODRÍGUEZ JIMÉNEZ (Studia Historica: Historia Contemporánea, 2013)
Between the end of the franquism and our days, the spanish extreme-right has suffered a resource and influence capacity depletion in society, and has been forced to renew their program and the way of making policy. The right-wing extremism was the srongly defeated during the transition from Franco’s dictatorship to democracy. As a consecuence of the economic and cultural changes and the weakness of spanish nationalism, the neofranquists and neofascists’ programs garnered a resounding rejection at the polls. The failure of 23-F coup attempt plunged the neofranquism into a crisis from which it has never recovered. The growth of the xenophobic extreme-right in Europe, something that had not occurred since the end of World War ii, has been a determining factor, long overdue, for the renewal of programs also in Spain that are now based on the uptake of the xenophobic vote. No extreme-right party has achieved between 1982 and 2012 representation in the spanish legislative assembly. This situation contrasts with what happens in other European countries and that is what we are trying to explain. However, the increased receptivity to the xenophobic discourse has allowed a political party that copied le Pen’s program and is specialiced in the islam rejection, to obtain representation in several municipalities of Cataluña. That way (municipal elections, to try to jump into the regional ones) is the one that cur-rently offers more possibilities of growth to the extreme-right in Spain.